Kemampuan Siswa Menelaah Struktur dan Kaidah Kebahasaan Teks Drama Kelas VIII SMP Negeri 5 Tambang Kampar - Destriyana, Destriyana; Mukhlis, Muhammad; Piliang, Wilda Srihastuty Handayani; Latif, Latif (UIR Press, 2023)
This study aims to test students' abilities in analyzing the structure of drama texts and linguistic conventions in drama texts in class VIII students of SMPN 5 Tambang Kampar in the 2019/2020 academic year. Based on the results of data analysis and discussion conducted, students' ability to analyze the structure of drama texts can be categorized as good with an average score of 87.88. However, students' ability to analyze linguistic rules in drama texts is still quite good with an average score of 75.17. Even though most of the students could find the results of the linguistic rules of the drama text being tested, there were still some students who needed improvement in this regard. In order to improve students' ability to analyze language rules in drama texts, it is recommended that the school pay special attention to learning the language rules of drama texts for class VIII students of SMPN 5 Tambang Kampar. This can be done through more active learning strategies, such as group discussions, simulations, or role playing. In addition, the school can also hold special training for Indonesian language teachers to improve their ability to teach drama texts correctly and effectively. Thus, it is expected that students' ability to analyze linguistic rules in drama texts can be significantly improved.